Childrens Resilience in Single Parent Families: A Case Study in Tanjung Alam Village Asahan Regency - Alhadi Putra; Bahtiar Siregar (STAI Serdang Lubuk Pakam, 2025)
This study aims to examine the forms and factors that influence the resilience of children growing up in single-parent families in Tanjung Alam Village, Asahan Regency. Resilience is understood as the ability of individuals, in this case children, to survive, rise, and adapt positively despite facing pressure or life difficulties, such as the condition of an intact family. This research approach is qualitative with a case study method. Data were collected through in-depth interviews, observations, and documentation of several children from single-parent families as well as related parties such as parents and community leaders. The results show that children's resilience is formed through a combination of internal factors such as self-confidence, motivation, and hope for the future, as well as external factors such as emotional support from parents, social involvement, and a supportive school environment. Despite facing economic deprivation and psychological burdens, most children demonstrated good adaptive skills. This finding confirms the important role of the environment in supporting children's psychological resilience in non-ideal family conditions.